2019
DOI: 10.1002/asi.24332
|View full text |Cite
|
Sign up to set email alerts
|

How different Are crowdfunders? Examining archetypes of crowdfunders

Abstract: We unpack the complexities of the crowdfunder community by identifying different archetypes of crowdfunders funding technology projects on Kickstarter. com. Drawing on the extant literature on innovation adoption and opinion leadership, we propose two dimensions of crowdfunders that capture the heterogeneity in crowdfundersʼ behavior: opinion leadership and interest specialization of crowdfunders. Using a set of variables representing these two dimensions, our analysis revealed five distinct archetypes of crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…Following prior research using LDA topic modeling (e.g. Geva et al , 2019; Lin and Boh, 2020), we set the Dirichlet hyperparameters, α = 0.1 and ß = 0.01 and the number of iterations to 1,000.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following prior research using LDA topic modeling (e.g. Geva et al , 2019; Lin and Boh, 2020), we set the Dirichlet hyperparameters, α = 0.1 and ß = 0.01 and the number of iterations to 1,000.…”
Section: Methodsmentioning
confidence: 99%
“…Sellers' performance may vary across different online identities. For instance, in the context of online crowdfunding, researchers found that crowdfunding projects' performance differed by the creator identity types and suggested platform operators attracting and promoting different project creators (Lin and Boh, 2020; Ryu and Kim, 2018). Although prior research suggests that sellers' identity signaling may predict their sales performance (Verbeke et al , 2011), how different online identities are related to sales performance has not been empirically studied.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in another stream of the literature, scholars have examined project backers' role in crowdfunding project success. Some of these researchers have investigated backers' motivations for supporting crowdfunding projects (Baber and Fanea-Ivanovici, 2023;Bretschneider and Leimeister, 2017;B€ urger and Kleinert, 2021;Lin and Boh, 2020). Meanwhile, some scholars have studied backers' crowdfunding-related behaviors, such as herding behavior (Liu et al, 2015;Kim et al, 2020;Saxton and Wang, 2014) and funding decisions (Gleasure and Feller, 2018;Kromidha and Robson, 2016;Lin and Viswanathan, 2016).…”
Section: Theoretical Background 21 Crowdfundingmentioning
confidence: 99%
“…The prior literature has shown that crowdfunding project success is associated with various factors related to the three different actors involved in crowdfunding (Efrat and Gilboa, 2020;Deng et al, 2022;Baber and Fanea-Ivanovici, 2023;Coakley et al, 2022). However, the authors of previous studies have mainly examined factors related to platforms, project owners, or project backers (Kl€ ohn, 2018;Clauss et al, 2018;Lin and Boh, 2020). Few researchers have yet examined crowdfunding project success through factors related to both project owners and backers, though such an approach could explain their different roles in depth.…”
Section: Theoretical Background 21 Crowdfundingmentioning
confidence: 99%